IMF Glossary : English-French-Arabic, Third edition. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The main body of the Glossary consists of terms, phraseological units, and institutional titles covering areas such as macroeconomics, money and banking, public finance, taxation, balance of payments, statistics, accounting, and economic development.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Informal Economy; Monetary Policy; Underground Econom